1996
DOI: 10.2172/211349
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Hanford Combination Neutron Dosimeter in plutonium environments

Abstract: T h i s report documents response characteristics and the development of dose algorithms for the Hanford Combination Neutron Dosimeter (HCND) implemented on January 1, 1995. The HCND was accredited under the U.S. Department o f Energy (DOE) Laboratory Accreditation Program (DOELAP) during 1994. The HCND employs two neutron dose components consisting o f 1) an albedo thermoluminescent dosimeter (TLD) , and 2) a track-etch dosimeter (TED). Response characteristics of these two dosimeter components were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 1 publication
0
24
0
Order By: Relevance
“…These irradiations were performed in the Hanford Calibration Laboratory. A plutonium algorithm was developed from dosimeter irradiations at the PFP using plutonium sources (Endres et al 1996).…”
Section: Dosimeter Calibration Sources and Calibration Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…These irradiations were performed in the Hanford Calibration Laboratory. A plutonium algorithm was developed from dosimeter irradiations at the PFP using plutonium sources (Endres et al 1996).…”
Section: Dosimeter Calibration Sources and Calibration Factorsmentioning
confidence: 99%
“…In the 1995 study of Hanford dosimeter responses in the workplace (Endres et al 1996), Section 6.1 describes the use of this type of sphere measurement in neutron fields. This study found that 8 in.-to-3 in.…”
Section: Sphere Measurementsmentioning
confidence: 99%
See 3 more Smart Citations